Reformasi Administrasi Desa - Yudiatmaja, Wayu Eko; Samnuzulsari, Tri (Jurnal Ilmu Administrasi Negara (JUAN), 2015)
Reformasi Administrasi Desa   Tri Samnuzulsari(3nuzulsari@gmail.com) (Jurusan Sosiologi FISIP UMRAH) Wayu Eko Yudiatmaja(wayuguci@gmail.com) (Jurusan Ilmu Administrasi Negara FISIP UMRAH)   Abstract: This paper discuss about the reformation of village administration. Stressing of this paper are; conteptual foundation (what and how the reformation of village administration), rationale, function, the role of the reformation of village administration, and strategy for implementing the reformation of village administration on the village governance in Indonesia.